Active Mediation of Plasmon Enhanced Localized Exciton Generation, Carrier Diffusion and Enhanced Photon Emission - Sharmin Haq (Nature Portfolio, 2017)
Abstract Understanding the enhancement of charge carrier generation and their diffusion is imperative for improving the efficiency of optoelectronic devices particularly infrared photodetectors that are less developed than their visible counterpart. Here, using gold nanorods as model plasmonic systems, InAs quantum dots (QDs) embedded in an InGaAs quantum well as an emitter, and GaAs as an active mediator of surface plasmons for enhancing carrier generation and photon emission, the distance dependence of energy transfer and carrier diffusion have been investigated both experimentally and theoretically. Analysis of the QD emission enhancement as a function of distance reveals a Förster radius of 3.85 ± 0.15 nm, a near-field decay length of 4.8 ± 0.1 nm and an effective carrier diffusion length of 64.0 ± 3.0 nm. Theoretical study of the temporal-evolution of the electron-hole occupation number of the excited states of the QDs indicates that the emission enhancement trend is determined by the carrier diffusion and capture rates.